Effect of Coolant Jet Holes Direction on Film Cooling Performance (University of Thi-Qar Journal for Engineering Sciences, 2014)
The film cooling effectiveness and local heat transfer coefficient for coolant jet holes direction (orientation angle), have been investigated. Experimental investigations were done on a flat plate by using a single test transient IR thermograph technique.Evaluation of the cooling performance is obtained by estimated both film cooling effectiveness and heat flux ratios. Threemodelsof coolant jet holes are investigated,each model consists of two rows of holes arranged in a staggered way with different orientation angles. Model (1) downstream row with acute angle and the upstream row with obtuse angle; model (2) both rows with obtuse angles, while model (3) both rows with acute angles.The holes diameter is 4mm, the longitudinal distance between the upstream and downstream rows (X/D) is 4D, and the span distance between two neighboring holes (S/D) is 3D. Three blowing ratios of (BR= 0.5, 1.0, and 1.5) were used in the investigation program.In order to predict the flow behavior numerically for the cases under investigation CFDcode is introduced.The numerical investigation shows two large vortices large counter rotating vortex pair and horseshoe vortices ,both vortices have major effects on cooling performance.The experimental results showed that the film cooling effectiveness increases as blowing ratio increases for models (1 and 2), while decreases for model(3), and model (1) provide better performance than the others at high blowing ratios.